Uma espiral elitista de afirmação corporativa: blindagens e criminalizações a partir do imbricamento das disputas do sistema de justiça paulista com as disputas da política convencional - Cardoso, Luciana Zaffalon Leme (2017)
Considering the concept of democracy proposed by Boaventura de Sousa Santos, understood as a 'system that transforms unequal power into shared authority' (2016), and starting from the hypothesis that the Justice System can both favor and hamper the democratic deepening, the study proposes to unveil the politicization processes of São Paulo State Justice System, in order to understand how it affects the regional democratic process. The research covers the last two administrations of the São Paulo State Court of Justice´s, Public Ministry´s and Public Defender's Offices, from the beginning of 2012 to June 2016, and analyzes the social impacts of Justice administration in the fields of Public Security and the Penitentiary System, which are brought to the debate to put the analyzed issues in context. As the disputes for the control of Justice administration are structured according to political parties, embedded in the remuneration and corporate guidelines of legal careers, we propose to shift the focus from the judicialization of politics as the key element to explain the separation of powers, to enlighten the effects of the Executive Power agenda into the institutions of justice. In this context, the influence of political decision-making on judicial independence is explored considering practices that are not usually seen in the discussion about the formal and normative dynamics of separation of powers.